Application of Self Reflection Mirror Technique on Self-Acceptance among Post-Mastectomy Breast Cancer Patients Using Roy Adaptation Model - Nopita Dwi Ramadanti; Meri Epriana Susanti (Multidisciplinary Journals, 2026)
. Breast cancer is one of the most common malignancies affecting women worldwide and frequently requires mastectomy as a definitive treatment. Although mastectomy is effective in controlling disease progression, it often results in significant physical and psychological consequences, particularly disturbances in self-concept and self-acceptance. Impaired self-acceptance may negatively affect psychological adaptation, coping mechanisms, and overall quality of life in post-mastectomy patients.This study aimed to describe the application of the Self Reflection Mirror technique in improving self-acceptance among post-mastectomy breast cancer patients through the framework of Roy Adaptation Model (RAM). A qualitative case study design with a phenomenological approach was employed involving two post-mastectomy breast cancer patients treated at RSUD Dr. M. Yunus Bengkulu. Data were collected through in-depth interviews, observation, and nursing documentation. The Self Reflection Mirror intervention was implemented for three consecutive days based on Roy’s self-concept mode.The findings demonstrated an improvement in patients’ self-acceptance, reflected by reduced mirror avoidance, increased positive self-affirmation, improved body image perception, and greater willingness to engage in social interactions. The application of Roy Adaptation Model facilitated adaptive coping responses to physical and psychological changes following mastectomy. This study concludes that the Self Reflection Mirror technique is a beneficial psychosocial nursing intervention to enhance self-acceptance among post-mastectomy breast cancer patients.